Towards a muon collider - Carlotta Accettura; Dean Adams; Rohit Agarwal; Claudia Ahdida; Chiara Aimè; Nicola Amapane; David Amorim; Paolo Andreetto; Fabio Anulli; Robert Appleby; Artur Apresyan; Aram Apyan; et al. (European Physical Journal C: Particles and Fields, 2023)
Abstract A muon collider would enable the big jump ahead in energy reach that is needed for a fruitful exploration of fundamental interactions. The challenges of producing muon collisions at high luminosity and 10 TeV centre of mass energy are being investigated by the recently-formed International Muon Collider Collaboration. This Review summarises the status and the recent advances on muon colliders design, physics and detector studies. The aim is to provide a global perspective of the field and to outline directions for future work.